Peran Agen Moderasi Beragama dalam Upaya Peningkatan Kerukunan Umat Beragama - Priyono, Eko (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
This policy paper reviews religious moderation as one of the Ministry of Religious Affairs priority programs as stated in the Ministry of Religious Affairs’s Strategic Plan for 2020-2024. This paper uses a qualitative method with a descriptive analysis approach, where data is collected, grouped, and analyzed using descriptive analysis. Data shows that starting in 2019, the Ministry of Religious Affairs began pioneering programs to mainstream religious moderation to enlighten in the context of developing religious perspectives, attitudes, and practices with a middle way, creating and building peace, respecting diversity, respecting human dignity, and upholding adab. the glory of human life which is manifested in an attitude of life that is trustworthy, fair, full of compassion, tolerance, without discrimination, and mutual respect for diversity. In efforts to increase religious moderation, religious moderation agents are needed who act as agents who spread important echoes or echoes of the implementation of religious moderation in everyday social life, so that harmony can be created between and among religious communities. Thus, the author recommends strengthening religious moderation not only within the scope of the Ministry of Religious Affairs, Ministries/Institutions, and local governments, but it is also important to create religious moderation agents by involving stakeholders, such as religious leaders and community leaders in society.